Virus-like particles associated with porcine epidemic diarrhoea - Chasey, D. (Res Vet Sci, 1978)
Porcine epidemic diarrhoea type II was reproduced in experimental pigs of various ages by oral dosing with minced intestine from a naturally occurring case of the disease. Virus-like particles which probably represent an unidentified coronavirus were seen by electron microscopy in the faeces and intestinal epithelium of infected animals.